2016
DOI: 10.5194/esurf-4-47-2016
|View full text |Cite
|
Sign up to set email alerts
|

Storm-triggered landslides in the Peruvian Andes and implications for topography, carbon cycles, and biodiversity

Abstract: Abstract. In this study, we assess the geomorphic role of a rare, large-magnitude landslide-triggering event and consider its effect on mountain forest ecosystems and the erosion of organic carbon in an Andean river catchment. Proximal triggers such as large rain storms are known to cause large numbers of landslides, but the relative effects of such low-frequency, high-magnitude events are not well known in the context of more regular, smaller events. We develop a 25-year duration, annual-resolution landslide … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 105 publications
(203 reference statements)
5
71
0
Order By: Relevance
“…9a). Increased incidence of landslides in the Andes during the months leading up to April, i.e., the Amazon rainy season, would increase the input of high altitude 13 C-enriched POC from these tributaries to Óbidos (Clark et al, 2013;Clark et al, 2016). The higher N:C of POC in this sampling month would also imply that these sources are more degraded (Ometto et al, 2006;Cleveland and Liptzin, 2007), consistent with lower bulk and RPO gas fraction F m values observed for the Solimões and Madeira river samples.…”
Section: Radiocarbon Distribution Of Poc Flux At óBidossupporting
confidence: 63%
“…9a). Increased incidence of landslides in the Andes during the months leading up to April, i.e., the Amazon rainy season, would increase the input of high altitude 13 C-enriched POC from these tributaries to Óbidos (Clark et al, 2013;Clark et al, 2016). The higher N:C of POC in this sampling month would also imply that these sources are more degraded (Ometto et al, 2006;Cleveland and Liptzin, 2007), consistent with lower bulk and RPO gas fraction F m values observed for the Solimões and Madeira river samples.…”
Section: Radiocarbon Distribution Of Poc Flux At óBidossupporting
confidence: 63%
“…The climate and tectonic setting combine to produce moderate-to-high denudation rates of~0.4 mm yr À1 in the central Andes according to cosmogenic radionuclide concentrations in detrital quartz [Wittmann et al, 2009] and decadal river gauging [Guyot et al, 1996]. The slopes are steep and prone to landslides, which harvest sediment and POC [Blodgett and Isacks, 2007;Clark et al, 2016]. In this part of the Andes, rivers drain large areas of sedimentary and meta-sedimentary melanges that comprise~80% of the Kosñipata River drainage area [Clark et al, 2013].…”
Section: Study Areamentioning
confidence: 99%
“…We aim to provide new insight into the impact of physical erosion on carbon budgets by quantifying the source and magnitude of river discharge of POC from the steep, eastern flank of the Peruvian Andes, characterized by predominantly sedimentary bedrock with relatively high concentrations of petrogenic organic carbon. We focus on a catchment where previous work has established the hydrological water balance [Clark et al, 2014]; rates of geomorphic processes such as landslides ; and forest productivity, respiration, and carbon stocks across the landscape [Zimmermann et al, 2009;Zimmermann et al, 2010a;Marthews et al, 2012;Girardin et al, 2014b;Clark et al, 2016;Malhi et al, 2016]. We use a detailed set of suspended sediment samples and hydrometric river gauging measurements over a 12 month period and analyze the stable isotopes of POC (δ 13 C org ), the nitrogen to organic carbon ratio ([N]/[OC total ]), and the radiocarbon activity of POC to distinguish POC petro derived from sedimentary rocks and to study the source and age of POC biosphere .…”
Section: Introductionmentioning
confidence: 99%
“…Fluvial evacuation of landslide-derived sediment removes mass from mountains, influencing landscape evolution [Pearce and Watson, 1986;Malamud et al, 2004;Korup et al, 2007;Hovius et al, 2011;Parker et al, 2011;Egholm et al, 2013;Li et al, 2014]. Landslides also impact the terrestrial biosphere [Garwood et al, 1979;Allen et al, 1999;Clark et al, 2016], and delivery of eroded material to river channels can redistribute essential nutrient elements (e.g., carbon and nitrogen), contributing to tectonic forcing of global biogeochemical cycles Ramos Scharrón et al, 2012;Jin et al, 2016]. Furthermore, sediment supply from landslides to rivers may cause prolonged secondary natural hazards, via channel aggradation and enhanced flooding, and may reduce the storage capacity of downstream reservoirs [Korup et al, 2004;Glade and Crozier, 2005;Huang and Fan, 2013;Wang et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of landslide spatial distribution have measured landslide locations with respect to channels versus ridges, demonstrating that landslides cluster in specific landscape positions depending on hillslope topography and the landslide triggering mechanism, e.g., earthquake versus rainstorm [Densmore and Hovius, 2000;Meunier et al, 2008;Huang and Montgomery, 2014]. Other studies have distinguished landslides that are "visibly connected" to river channels and presumably available for fluvial transport West et al, 2011;Clark et al, 2016]. For the 1999 M w 7.6 Chi-Chi earthquake in Taiwan, an estimated 8% of the earthquaketriggered landslide population was connected to channels [Dadson et al, 2004], and this connectivity showed little spatial variability .…”
Section: Introductionmentioning
confidence: 99%